2019
DOI: 10.3390/cancers11070969
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Albumin-Stabilized Gold Nanoclusters for the Reduction of Cancer Stem Cells

Abstract: Controlled delivery of multiple chemotherapeutics can improve the effectiveness of treatments and reduce side effects and relapses. Here in, we used albumin-stabilized gold nanoclusters modified with doxorubicin and SN38 (AuNCs-DS) as combined therapy for cancer. The chemotherapeutics are conjugated to the nanostructures using linkers that release them when exposed to different internal stimuli (Glutathione and pH). This system has shown potent antitumor activity against breast and pancreatic cancer cells. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…However, no evidence is available on the biologically relevance of serum albumin for NPs in complex media like serum. Nevertheless, presently, HSA is one of the most promising components for effective drug carriers and nanotheranostics ( 52 , 53 ).…”
Section: Influence On Np-cell Interactions Of Specific Np-bound Protementioning
confidence: 99%
“…However, no evidence is available on the biologically relevance of serum albumin for NPs in complex media like serum. Nevertheless, presently, HSA is one of the most promising components for effective drug carriers and nanotheranostics ( 52 , 53 ).…”
Section: Influence On Np-cell Interactions Of Specific Np-bound Protementioning
confidence: 99%
“…Neutral red (0.5%) was then added at a volume of 100 ml to each well and stained for 2 minutes. The stains were washed out with PBS and immediately observed under an inverted microscope (Latorre et al, 2019).…”
Section: Morphological Changes In Treated Cellsmentioning
confidence: 99%
“…AuNCs with the 6-mercaptohexanoic acid (MHA) ligands were prepared according to a reported method. 14,20 In brief, HAuCl 4 (20 mM, 0.25 mL) and MHA (10 mM, 1 mL) were mixed with 3.35 mL water to form an Au-MHA complex, which was then dissolved by addition of NaOH solution (1 M, 0.3 mL). A freshly prepared NaBH 4 solution (112 mM, 0.1 mL) was added into the Au-MHA complex.…”
Section: Synthesis and Characterization Of Auncsmentioning
confidence: 99%
“…AuNCs were synthesized by NaBH 4 reduction method. 14,19 The TEM images showed that AuNCs were spherical and well monodispersed ( Figure 1A). The core size below 2 nm was observed by TEM.…”
Section: Characterization Of Auncsmentioning
confidence: 99%
See 1 more Smart Citation